A strip line ring resonator for dielectric properties measurement of thin fabric. Issue 11 (15th October 2021) - Tu, Huating; Zhang, Yaya; Hong, Hong; Hu, Jiyong; Ding, Xin
Abstract: Measuring the dielectric properties of the fabric is much important when it is used as a substrate material for flexible electronic devices. However, the classical resonant cavity is not accurate for thin fabric measurement. This article applied the strip line ring resonator principle, which was successfully used to measure the dielectric constant of the thin film. The ring resonator was constructed by 12-layer fabric stacked together with single-side copper-etched RO5880 substrate. The resonant frequency and Q factor were measured and compared with finite element simulation results, and then the dielectric constant and loss were accurately deduced. First, a RO5880 was used as the unknown substrate to replace the fabric to verify its accuracy, and the relative error of dielectric constant and loss is 0.9% and 5.6%, respectively. And then, the same method was used to measure the fabric. As a result, the dielectric constant and loss tangent of fabric were 2.4 ± 0.05 and 0.05 ± 0.01, respectively.